Preferences in Choosing Thesis Topics and Advisors Sociology Students, Faculty of Social and Political Sciences, Universitas Riau - Achmad Hidir; Teguh Widodo; Dian Kurnia Anggreta; Robi Armilus; Rufaidah Syafawani (Tradition and Modernity of Humanity, 2025)
One of the requirements for graduation is writing a thesis. Choosing the right topic and supervisor is crucial for producing high-quality research. This study analyzes the factors influencing students' choice of thesis topic and supervisor using a qualitative approach. The participants involved in this study consisted of 11 students from the 2022 cohort, without distinguishing gender and other social backgrounds, and were selected purposively, with the criterion of having completed a proposal seminar. The data collection process was conducted through semi-structured interviews that allowed participants to provide in-depth answers and explain their perspectives on the selection of thesis topics and supervisors. Data analysis used thematic analysis to identify patterns that emerged from the participants' responses. The results of this study found that the preferences for selecting thesis topics and supervisors among Sociology students at the Faculty of Social and Political Sciences, Riau University, were greatly influenced by various factors, including the relevance of social issues, the background of the supervisor, and a good supervisory approach. Students tend to choose topics that are trendy in line with current developments and want support from lecturers who have an emotional connection with students and are experienced in their chosen field.